2020
DOI: 10.1016/j.cgh.2019.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Inflammatory Bowel Diseases Throughout Latin America and the Caribbean: A Systematic Review

Abstract: BACKGROUND & AIMS:The incidence of inflammatory bowel diseases (IBD) is increasing in Latin America. We performed a systematic review to identify clinical and epidemiologic features of IBD in Latin America (including Mexico, Central America, and South America) and the Caribbean. METHODS:We searched MEDLINE, EMBASE, and SciELO databases for clinical or epidemiologic studies of Crohn's disease (CD) or ulcerative colitis (UC) from Latin American and Caribbean countries and territories that reported incidence, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
99
1
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(121 citation statements)
references
References 30 publications
5
99
1
16
Order By: Relevance
“…13 These findings are compatible with the data from a recently published systematic review, which found that the prevalence of inflammatory bowel disease has been increasing in Latin America and Carribbean. 14 Ulcerative colitis was more prevalent than Crohn's disease, which is consistent with previous data from other countries, but discordant with previous Brazilian studies. 1,7 Unlike in some older Brazilian case series, which showed predominance of proctosigmoiditis and left hemicolitis, 7 pancolitis predominated in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…13 These findings are compatible with the data from a recently published systematic review, which found that the prevalence of inflammatory bowel disease has been increasing in Latin America and Carribbean. 14 Ulcerative colitis was more prevalent than Crohn's disease, which is consistent with previous data from other countries, but discordant with previous Brazilian studies. 1,7 Unlike in some older Brazilian case series, which showed predominance of proctosigmoiditis and left hemicolitis, 7 pancolitis predominated in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Historically, IBD typically emerges in a population as cases of ulcerative colitis, eventually followed by cases of Crohn's disease. Over time, Crohn's disease becomes more commonly diagnosed as the incidence approximates and, in some cases, surpasses that of ulcerative colitis 49 . For example, in Malaysia the ulcerative colitis to Crohn's disease ratio was 5:1 in the 1980s and fell to 1.7:1 from 2010 to 2018 (reF.…”
Section: Nature Reviews | Gastroenterology and Hepatologymentioning
confidence: 99%
“…Over the last decades, the incidence and prevalence of IBD seem to be increasing in our country, in a profile that seems different than other Latin American countries (7,8) . As compared to countries such as Colombia, Mexico, and Argentina, the UC:CD ratio in Brazil is proximal to one in different areas of the federation, a similar disease distribution as countries from North America and Europe (9) . This means that we have more cases of CD than other countries in the same continent, a characteristic that is observed in more developed areas of the world.…”
mentioning
confidence: 89%